BMP4 gene therapy enhances insulin sensitivity but not adipose tissue browning in obese mice - Jenny M. Hoffmann; John R. Grünberg; Ann Hammarstedt; Tobias Kroon; Thomas U. Greiner; Stefanie Maurer; Ivet Elias; Vilborg Palsdottir; Fatima Bosch; Jeremie Boucher; Shahram Hedjazifar; Ulf Smith (Molecular Metabolism, 2020)
Objective: Bone morphogenetic protein 4 (BMP4) adeno-associated viral vectors of serotype 8 (AAV8) gene therapy targeting the liver prevents the development of obesity in initially lean mice by browning the large subcutaneous white adipose tissue (WAT) and enhancing energy expenditure. Here, we examine whether this approach could also reduce established obesity. Methods: Dietary-induced obese C57BL6/N mice received AAV8 BMP4 gene therapy at 17–18 weeks of age. They were kept on a high-fat diet and phenotypically characterized for an additional 10–12 weeks. Following termination, the mice underwent additional characterization in vitro. Results: Surprisingly, we observed no effect on body weight, browning of WAT, or energy expenditure in these obese mice, but whole-body insulin sensitivity and glucose tolerance were robustly improved. Insulin signaling and insulin-stimulated glucose uptake were increased in both adipose cells and skeletal muscle. BMP4 also decreased hepatic glucose production and reduced gluconeogenic enzymes in the liver, but not in the kidney, in addition to enhancing insulin action in the liver. Conclusions: Our findings show that BMP4 prevents, but does not reverse, established obesity in adult mice, while it improves insulin sensitivity independent of weight reduction. The BMP antagonist Noggin was increased in WAT in obesity, which may account for the lack of browning. Keywords: Obesity, Gene therapy, Insulin sensitivity, Adipose tissue, Skeletal muscle, Liver